Nicolae Iorga (1871-1940) (Confluenţe Bibliologice, 2020)
The article includes materials about the re-edition of two volumes written by Nicolae Iorga on the 100th anniversary of its publication Neamul Românesc în Bucovina (The Romanian people in Bucovina) and Neamul Românesc în Basarabia (The Romanian people in Bessarabia) at SEMN Publishing House. From the ﬁrst book we learn travel stories, impressions, many images, events that took place among the people of Bucovina, but also many interesting historical data highlighted by the historian.
Keywords: Nicolae Iorga (1871-1940); history of Bessarabia; Romanian history